Simvastatin Improves the Jaw Bone Microstructural Defect Induced by High Cholesterol Diet in Rats by Regulating Autophagic Flux. (27th June 2018) - Zhou, Jianhua; Gao, Xiaoli; Huang, Shengyun; Ma, Li; Cui, Yanjun; Wang, Hengkun; Qiu, Jianzhong; Wang, Lili; Dong, Quanjiang; Chen, Zhenggang; Wang, Xuxia; Zhang, Dongsheng
Abstract : Objective. The objective of this study is to evaluate the effect of simvastatin on the jaw bone microstructural defect and autophagy in rats with high cholesterol diet (HCD). Methods. Male Sprague-Dawley rats were fed a standard rodent chow (NC group) or a high cholesterol diet for 32 weeks and the HCD-fed rats were treated with vehicle (HC group) or simvastatin (5 mg/kg orally daily for 8 weeks, HC + SIM group, andn = 10 /group). The static histomorphometric changes in the jaw bone tissues in individual rats were evaluated. The relative levels of OPG, RANKL, NF- κ B, LC3, and p62 in the jaw bone tissues were determined by quantitative RT-PCR and/or immunohistochemistry. Results. Compared with the NC group, the HC groups had lower trabecular bone volume, trabecular thickness and trabecular number, and increased ratios of RANKL/OPG in the jaw bone, accompanied by enhanced NF- κ B activation and autophagy. Simvastatin treatment inhabited these changes, including the decreased levels of serum proinflammatory cytokines and increased autophagy. Conclusion. Simvastatin treatment could inhibit the hyperlipidemia-induced jaw bone microstructural defect in rats by increasing autophagic flux.